A mechanistic evaluation of antioxidant nutraceuticals on their potential against age-associated neurodegenerative diseases - Nur Zuliani Ramli; Mohamad Fairuz Yahaya; Ikuo Tooyama; Hanafi Ahmad Damanhuri (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
Nutraceuticals have been extensively studied worldwide due to its neuroprotective effects in in vivo and in vitro studies, attributed by the antioxidative properties. Alzheimer (AD) and Parkinson disease (PD) are the two main neurodegenerative disorders that are discussed in this review. Both AD and PD share the similar involvement of oxidative stress in their pathophysiology. Nutraceuticals exert their antioxidative effects via direct scavenging of free radicals, prevent damage to biomolecules, indirectly stimulate the endogenous antioxidative enzymes and gene expressions, inhibit activation of pro-oxidant enzymes, and chelate metals. In addition, nutraceuticals can act as modulators of pro-survival, pro-apoptotic, and inflammatory signaling pathways. They have been shown to be effective particularly in preclinical stages, due to their multiple mechanisms of action in attenuating oxidative stress underlying AD and PD. Natural antioxidants from food sources and natural products such as resveratrol, curcumin, green tea polyphenols, and vitamin E are promising therapeutic agents in oxidative stress-mediated neurodegenerative disease as they have fewer adverse effects, more tolerable, cheaper, and sustainable for long term consumption.